An axiomatics for multivalued dependences in tabular databases - Redko, V.N.; Bui, D.B.; Puzikova, А.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Axiomatics for multivalued dependences in table databases and for functional and multivalued dependences is considered. The completeness of these axiomatic systems is established in terms of the coincidence of syntactic and semantic consequence relations. The completeness criteria for these axiomatic systems are formulated in terms of cardinalities of the universal domain and the set of attributes.